ANALYSIS OF MICRONUTRIENT INTAKE, MATERNAL WEIGHT GAIN DURING PREGNANCY, AND PASSIVE SMOKER ON NONSYNDROMIC OROFACIAL CLEFT INCIDENCE AT HARAPAN KITA WOMEN AND CHILDREN HOSPITAL - Rosa, Sonya; Ekayanti, Ikeu; Tanziha, Ikeu; Syafrudin Hak, Muhammad (Media Gizi Indonesia, 2025)
A congenital facial anomaly that manifests as a cleft lip, cleft palate, or both—without the involvement of other organ abnormalities—is known as a non-syndromic orofacial cleft (OFC) (Tobing, 2017). According to the Indonesian Ministry of Health (2019), OFC represents 0.2% of disabilities among Indonesian children aged 24 to 59 months. The causes of OFC are multifactorial. In Indonesia, approximately 7,500 new OFC cases are reported annually, with a rising trend (Purwitasari et al., 2020). This study aimed to investigate the association between micronutrient intake, maternal weight gain during pregnancy, and maternal exposure to secondhand smoke with the incidence of non-syndromic OFC. A case-control study was conducted at Harapan Kita Women and Children Hospital in Jakarta, involving 35 participants in both the case and control groups. Data were collected from both primary and secondary sources. Primary data were obtained through direct interviews with respondents, while secondary data were sourced from maternal and child health (MCH) books. Micronutrient intake was measured using a semi-quantitative food frequency questionnaire (SQ-FFQ). Data analysis was performed using Microsoft Excel 365 and SPSS version 25.0 for Windows, applying logistic regression. The findings indicated that low folic acid and zinc intake, insufficient maternal weight gain during pregnancy, and maternal exposure to secondhand smoke were significantly associated with the development of non-syndromic orofacial cleft (p < 0.05).